DAMPAK CORPORATE GOVERNANCE, FINANCIAL STABILITY, DAN FINANCIAL TARGET DALAM KECURANGAN LAPORAN KEUANGAN - Syafitri, Mawar; Ermaya, H.N.L; Putra, A.M (Jurnal Akunida, 2021)
This study aims to determine empirically the effect of corporate governance indicated by (board of commissioners, audit committee, managerial ownership, and institutional ownership), financial stability, and financial targets on financial statement fraud in manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. The sample selection used purposive sampling method and obtained 108 data samples. Hypothesis testing in this study using Multiple Linear Regression Analysis with SPSS version 25 program and a significance level of 5% (0.05). After a series of tests were conducted, the results showed that 1) the board of commissioners, audit committee, managerial ownership, institutional ownership, and financial targets had no significant effect on financial statement fraud; 2) financial stability has a significant positive effect on financial statement fraud.